Emphysematous pyelonephritis caused by Klebsiella oxytoca in a patient with diabetic nephropathy - (:unkn) unknown (My University, 2010)
A 50-year-old woman with a 30 years history of diabetes mellitus and has been diagnosed with diabetic nephropathy for the last 4 years presented with abdominal pain, nausea and vomiting. Abdominal ultrasonography revealed a hyperechogenic air image at right kidney and with the aid of subsequently performed abdominal tomography type 2 emphysematous pyelonephritis diagnosis was made. Klebsiella oxytoca was isolated in blood culture and with appropriate antibiotic therapy and subsequent percutenous drainage the patient made a full recovery.
Keywords: Diabetes mellitus; Emphysematous pyelonephritis; Klebsiella oxytoca